Berkouwer and catholicism : disputed questions - Echeverria, Eduardo J. (Studies in Reformed Theology, 2013)
Gerrit Cornelis Berkouwer (1903-1996) was a great master of dogmatic and ecumenical theology. He was a Reformed Protestant thinker, with roots in Dutch neo-Calvinism, a holder of the Chair in Dogmatics (1945-1974) at the Free University, Amsterdam, a position previously held by his two illustrious neo-Calvinist predecessors, Abraham Kuyper (1837-1920) and Herman Bavinck (1854-1921). Echeverria provides a much needed in-depth analysis and critique of his theology, particularly his evolving relationship with Catholicism in light of Vatican II. His contention is that Berkouwer's careful and nuanced examination of Catholic theology-as well as possible responses to his critiques-offers important clues for the contemporary ecumenical project.